Computation and visualization of uncertainty in surgical navigation. Issue 3 (3rd October 2013) - Simpson, Amber L.; Ma, Burton; Vasarhelyi, Edward M.; Borschneck, Dan P.; Ellis, Randy E.; James Stewart, A.
Abstract Background Surgical displays do not show uncertainty information with respect to the position and orientation of instruments. Data is presented as though it were perfect; surgeons unaware of this uncertainty could make critical navigational mistakes. Methods The propagation of uncertainty to the tip of a surgical instrument is described and a novel uncertainty visualization method is proposed. An extensive study with surgeons has examined the effect of uncertainty visualization on surgical performance with pedicle screw insertion, a procedure highly sensitive to uncertain data. Results It is shown that surgical performance (time to insert screw, degree of breach of pedicle, and rotation error) is not impeded by the additional cognitive burden imposed by uncertainty visualization. Conclusions Uncertainty can be computed in real time and visualized without adversely affecting surgical performance, and the best method of uncertainty visualization may depend upon the type of navigation display. Copyright © 2013 John Wiley & Sons, Ltd.